PHOrming the inflammasome: phosphorylation is a critical switch in inflammasome signalling - McKee, CM; Fischer, FA; Bezbradica, JS; Coll, RC (Biochemical Society, 2021)
Inflammasomes are protein complexes in the innate immune system that regulate the production of pro-inflammatory cytokines and inflammatory cell death. Inflammasome activation and subsequent cell death often occur within minutes to an hour, so the pathway must be dynamically controlled to prevent excessive inflammation and the development of inflammatory diseases. Phosphorylation is a fundamental post-translational modification that allows rapid control over protein function and the phosphorylation of inflammasome proteins has emerged as a key regulatory step in inflammasome activation. Phosphorylation of inflammasome sensor and adapter proteins regulates their inter- and intra-molecular interactions, subcellular localisation, and function. The control of inflammasome phosphorylation may thus provide a new strategy for the development of anti-inflammatory therapeutics. Herein we describe the current knowledge of how phosphorylation operates as a critical switch for inflammasome signalling.